Investigation of the Initial Condition of Motion for Non-Uniform Sediments - Shital Patage, Rakesh Kumar, Abhay Shelar, Supriya Shinde (Mathematical Statistician and Engineering Applications, 2020)
Experiments on the beginning motion condition and bed capacity transport of different components for non-uniform sediment are presented in this paper. According to studies done for this study and by other researchers, the known relation for the critical tractive stress (CTS) of sediment mixture has certain upper and lower bounds. The best knowledge of hydraulic restrictions comes from experimental research into factors including flow rate, sediment transport capacity, bed depth, and critical shear stress. In this context, we investigate hydraulic limitations. At the APCOER Hydraulic Lab in Pune, experiments were carried out in the 10 meter long, 0.35 meter wide, and 0.50 meter deep inclined flume.